The effect of staining and vacuum sintering on optical and mechanical properties of partially and fully stabilized monolithic zirconia - Sulaiman TA; Abdulmajeed AA; Donovan TE; Vallittu PK; Narhi TO; Lassila LV (JAPANESE SOC DENTAL MATERIALS DEVICES, 2022)
The effect of staining and vacuum sintering on optical properties and the bi-axial flexural strength of partially and fully stabilized monolithic zirconia (PSZ, FSZ) were evaluated. Disc-shaped specimens divided into three subgroups (n=15): non-stained, stained and non-stained with vacuum sintering. After staining and sintering, optical properties were evaluated using a reflection spectrophotometer and bi-axial flexural strength was tested using the piston-on-three balls technique. Statistical analysis was performed using multivariate analysis of variance (MANOVA) followed by post-hoc Tukey's tests (p<0.05). Staining decreased translucency parameter (TP) values of FSZ (p<0.05). Sintering under vacuum enhanced TP values for PSZ (p<0.05). Staining enhanced surface gloss for both types of zirconia (p<0.05). Staining increased bi-axial flexural strength of FSZ (p<0.05), while it decreased the strength of PSZ (p<0.05). Sintering under vacuum provided minimal benefits with either type of zirconia.